Fahrenheit 451 [videorecording (DVD)] - Truffaut, François; Werner, Oskar, 1922-1984; Christie, Julie, 1941-; Cusack, Cyril, 1910-1993; Diffring, Anton, 1918-1989; Spenser, Jeremy, 1937-; Bradbury, Ray, 1920-2012 (Universal Studios, 2003)
Montag, a regimented fireman in charge of burning the forbidden volumes, meets a revolutionary school teacher who dares to read. Suddenly he finds himself a hunted fugitive, forced to choose not only between two women, but between personal safety and intellectual freedom.